Contribution of International Non-Governmental Organizations’ Interventions on Students’ Competence in English Language in Bugesera District Primary Schools, Rwanda - Ndikubwimana, Pierre; Mugiraneza, Faustin (African Journal of Education and Practice, 2024)
Purpose: The aim of the study was to evaluate the impact of interventions by International Non-Governmental Organizations on students' competence in Rwanda. Methodology: This research adopted a descriptive case study design aimed at establishing the impact of International Non-Governmental Organizations (INGOs) interventions on learners’ competence in English in Rwanda. The study utilized a mixed-method approach, incorporating both quantitative and qualitative methodologies to provide a comprehensive analysis. The population of our study was composed of 92 teachers and 16 head teachers of all primary schools in Bugesera District which were the target of Teacher Self Learning Academy project. The population also included 5 SEIs, 1 DEO/DDE in that district and a Plan International staff who has been involved in the TSLA project implementation. The sample size drawn from the total population of 92 teachers is 75 teachers using Slovin's Formula. Alongside the 8 head teachers from the selected schools, 5 SEIs, 1 DDE, and 1 Plan International staff member, this leads to a total of 90 participants for the study. The sampling approach was specifically tailored to suit the different categories of participants in the study. Purposive sampling was employed to select all head teachers from the identified schools. In contrast, stratified random sampling was used to select teachers, ensuring representativeness across various demographics such as gender, experience, and school location. For this study purpose, questionnaires and interview guide was used to collect and analyze data from research participants. The researcher took into consideration validity and reliability of the study to be valid and reliable to the audience. The researcher used descriptive statistics to analyze quantitative data and draw tables. Descriptive statistics were used to simplify large amounts of data. Inferential statistics were used to treat particular factors to detect the contribution of each determinant in learners’ competence in English. Primary data was treated through appropriate software as Statistical Package for Social Science (IBM/SPSS Version 21.0) and by after confronted with interviews and secondary data. Findings: The findings from both quantitative and qualitative data reveal that the TSLA project had a significant positive impact on students' English language skills, particularly in listening, speaking, reading, and writing. The findings revealed that 90.7% of the respondents agreed that instructional videos uploaded on iPods improved students' English listening skills, while 100% believed that these videos enhanced speaking fluency. Additionally, 94.7% of respondents indicated that the provision of teaching aids improved students' reading skills, and 86.7% noted an improvement in writing skills. Methods used in teachers' training, such as study groups and mentoring, were positively evaluated, with 76% and 74.7% of respondents, respectively, affirming their contribution to students’ English competence. However, challenges such as inadequate support from school management (62.7%), lack of incentives (88%), and insufficient resources (98.7%) were identified as barriers to effective implementation. Unique Contribution to Theory, Practice and Policy: The Government authorities should enforce policies that mandate continuous professional development for teachers and monitor their implementation to ensure effectiveness. The Ministry of Education should enhance teacher training programs by investing in comprehensive and continuous professional development programs that focus on modern teaching methodologies, ICT integration, and language competences. The Rwanda Basic Education Board (REB) should create incentive schemes to acknowledge and reward teachers who demonstrate exceptional dedication and improvement in their teaching practices. Bugesera Primary Schools should ensure that school management provides adequate support to teachers, including mentoring, peer coaching, and access to necessary teaching materials while parents should encourage and support their children's learning activities at home, particularly in using ICT tools and practicing language skills.